Meat myofibril: Chemical composition, sources and its potential for cardiac layers and strong skeleton muscle. Issue 1 (31st December 2022) - Khalid, Waseem; Arshad, Muhammad Sajid; Aslam, Noman; Majid Noor, Muhammad; Siddeeg, Azhari; Abdul Rahim, Muhammad; Zubair Khalid, Muhammad; Ali, Anwar; Maqbool, Zahra
ABSTRACT: Meat is the richest source of protein and according to meat sources, the protein is composed of different types of amino acids which are completely dependent upon the protein types. Myofibril is basically muscle protein that's widely present in different types of fish and low quantity is present in different meat (camel). Myofibril is made up of thick and thin myofilaments chemically. Actin, tropomyosin, troponin, and tropomyosin are thin myofilaments on the other hand myosin is only the thick myofilament. It is helpful in the formation of strong skeleton muscle and can also stronger and formation the cardiac layers (epicardium, myocardium and endocardium). Technologically, it can be used in the formation of different food products for the purpose of developing diet supplements. This review discussed different sources and chemical properties of myofibril protein and also its potential role toward the cardiac health. Myofibril's thick and thin filaments contribute in the construction of skeletal muscle and enhance the heart's protective coverings. The literature has been collected from Science Direct, Google Scholar and Web of Science. Myofibrils are made up of thick and thin filaments that can help in different human body functions. In the future, more research is necessary that discuss the close relation between myofibril protein and cardiac layers.